2017
DOI: 10.1097/inf.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-year Perspective of the Long-term Survival, CD4 Percentage and Social Achievements of Perinatally HIV-infected Children as a Function of Their Birth Era

Abstract: This first long-term follow-up study demonstrates remarkable survival and social skills of our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…48 Two-thirds had received an HS diploma or the equivalent, but only 19% were in college. 58 High rates of incarceration (12%) and homelessness (16%) were reported, reflecting the challenges faced by many YAs in poor, urban communities. 59 There are several limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…48 Two-thirds had received an HS diploma or the equivalent, but only 19% were in college. 58 High rates of incarceration (12%) and homelessness (16%) were reported, reflecting the challenges faced by many YAs in poor, urban communities. 59 There are several limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of these two studies we used the baseline outcomes of school functioning [ 44 , 47 ]. Studies with quantitative data compared the outcomes of school functioning of HIV-infected children with national norms (n = 15) [ 3 , 6 , 41 , 43 45 , 47 , 51 53 , 59 , 60 , 64 , 67 , 68 ], matched healthy controls (n = 3) [ 50 , 53 , 54 ], HIV-exposed uninfected children (n = 5) [ 46 , 52 , 57 , 59 , 68 ] or siblings or other children living in the same household (n = 4) [ 6 , 55 , 56 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies applied a previously validated instrument measuring multiple aspects of school functioning, which were summarized in one general school functioning scale [ 50 , 53 , 58 , 59 , 63 , 65 ]. Other studies evaluated aspects of school functioning through self-designed questionnaires (n = 7) [ 3 , 45 , 54 – 56 , 61 , 62 ], reviews of medical records (n = 6) [ 42 , 48 , 49 , 62 , 67 , 69 ] or interviews (n = 5) [ 8 , 51 , 52 , 66 , 69 ]. See S3 Appendix for an overview of general study characteristics and key findings per study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are only two reports examining similar milestones in longitudinal studies of YAPHIV and YAPHEU. In the Bellevue pediatric cohort study (birth years 1977–1978) conducted in New York City, 57% of YAPHIV, age 19 and older, had graduated high school or earned a GED [ 45 ]; YAPHEU were not included, thus limiting comparisons with the present study. Investigators with the Child and Adolescent Self‐Awareness and Health Study (CASAH; enrolment in 2003–2008) [ 46 ] reported on the attainment of young adult milestones among YAPHIV and YAPHEU, age 18–28 years, living in New York City: 67% graduated high school or earned a GED, 19% were in college, 42% were employed; 38% were neither in school nor working.…”
Section: Discussionmentioning
confidence: 99%